Pelindungan Hukum Terhadap Pekerja Rumah Tangga Yang Bekerja Di Luar Negeri Ditinjau Dari Undang - Undang Nomor 18 Tahun 2017 Dan Konvensi ILO 189 Tahun 2011 - Jelita R.T Banjarnahor; Agusmidah; Suria Ningsih (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Legal protection is defined as the recognition of the dignity, honour and human rights of legal subjects based on applicable legal provisions, covering both preventive and repressive aspects. This study specifically highlights the scope of legal protection for domestic workers, especially those working abroad. The crucial issue is the absence of specific laws that regulate and protect domestic workers, both at home and abroad, which results in domestic workers being vulnerable to exploitation and human rights violations. The research method used in this thesis is normative juridical. The main approach is the statute approach, reinforced by a conceptual and comparative approach. Data was collected through document/library studies (books, regulations, journals) and supported by interviews at BP2MI and PT. Wira Usaha Kreasi. This research is descriptive and analytical, linking existing regulations with relevant legal theories. The results of the study confirm that although domestic workers are much needed, they do not have adequate legal protection due to the absence of specific laws governing them, especially migrant domestic workers. This study emphasises the importance of government support in protecting the rights of domestic workers. The main recommendation is to pass the Draft Law (RUU) on Domestic Workers in accordance with the spirit of ILO Convention No. 189 on Decent Work. The government is encouraged to provide comprehensive social security and legal protection, as well as to impose strict sanctions on P3MI (Indonesian Migrant Worker Placement Companies) that neglect their responsibilities towards migrant domestic workers.